A contribuição das ONGs no âmbito da saúde: O caso das mulheres mastectomizadas na cidade de João Pessoa-PB - Morais, Veronaldo de Lucena (2010)
The social politics, throughout the years, veem in accordance with if modifying the adopted economic policies, being these politics mechanisms of reproduction of the work force. In this aspect, the intervention of the State goes in accordance with to present of differentiated form the conjuncture and the correlation of forces between the classrooms, form that, the more organized, more fortified they will become. From these relations where the State starts to intervened in the relations of the means of production and accumulation capital it, the third sector appears as half of mediation between the public and the private sector, occupying each time more spaces in such a way in the public sphere as in the private one. With the absence of the State in determined sectors of social order they emerge, in the third sector, the not Governmental Organizations ONGs supplying in many cases the paper of the State in the social relations. Leaving of this perspective, we search to understand this relation in the field of the health, specifically with women, cancer of mastectomizada breast and. Of the social point of view, we perceive that the cancer still is seen as an illness incurable what it unchains a series of negative feelings affecting its recovery. In this context, the civil society has formed nets in support to the health and solidarity the women with breast cancer. Through the action of the ONGs, in the most diverse areas, it is perceived mobilization, the motivation of volunteers next to these organizations, becoming basic in the support and the insertion of segments of the population estigmatizadas by the society.